Study on the Sources of Nosocomial Fungal Infections at Intensive Care Unit and Transplant Wards at a Teaching Hospital in Tehran - P Kordbacheh; F Zaini; P Kamali; K Ansari; M Safara (Tehran University of Medical Sciences, 2005)
The incidence of nosocomial fungal infections has increased dramatically during the past two decades as the consequence of continuous increase in the number of severely immunocompromised patients. This study was done to determine the presumptive sources of nosocomial fungal infections at the intensive care unit and transplant wards (in a university- based teaching hospital in Tehran) during a 10-month period. Totally 583 samples were obtained from the air, surfaces, health care workers and also from the patients at those wards. Mycological culture of the samples yielded growth of 25 different genus and species of fungi and the most common isolated fungi were Candida albicans, Penicillium spp., Aspergillus niger, and Cladosporium spp., respectively. It was noted that health care workers were carrying fungi on their hands (50 %), nasal mucosa (57.6%), in oral cavity (38.6%) and also by their shoes (92.3%) and uniforms (92.7%). Environmental fungal contamination was shown and it was more prominent at the intensive care unit. Hospitalization also had more significant effect on colonization of fungi in the patients at the latter ward. Therefore, the highly susceptible patients in present study were at the greatest risk of developing fungal infections and preventive measures were critical for prevention and control of these life-threatening fatal infections.